Respon Penawaran Hasil dan Permintaan Masukan Usahatani Padi: Suatu Pendugaan Ulang - Effendi Pasandaran; Pantjar Simatupang; nFN Supriyati (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1995)
Previous studies on rice farming output supply and input demand functions in Indonesia are considered not consistent anymore with present situation, and hence should be reestimated, because of two principle weaknesses: (1) hired tractor is not treated as a variable cost; (2) chemical fertilizers are not separated by their types. Reestimation is conducted using a quadratic profit function with crossprovincial-time series data 1986-1991. The analysis shows that TSP is a significant substitute for urea and complement with other chemical fertilizer. Human labor is substitutive with tractor and complementary with chemical fertilizers. As a whole, the findings are consistent with their theoretical expectation.